Proses Content Marketing Brand Partipost Indonesia dalam Mempertahankan Brand Engagement - Kasaya, Cindy Zafira; Lokananta, Arbi Cristional; Jati, Rocky Prasetyo; Wihardi, Doddy (Avant Garde, 2024)
Traditional marketing views customers as passive participants in interactions, but technology has transformed customers into active participants, allowing brands to engage with them more directly. One effective strategy that has been used by many companies is digital marketing through content marketing, and a notable example is the startup company Partipost. Partipost offers an influencer marketing platform that is utilized by both brands and consumers in various countries, including Indonesia. The company promotes itself by creating digital content through platforms such as its website, Partipost.com, and its Instagram account @partipost_id. Data collection for this study was conducted through participatory observation, documentation, and unstructured interviews with key sources from Partipost Indonesia during the period from July to December 2023. Based on result of this research, the overall content marketing process at Partipost Indonesia has successfully implemented the stages of content marketing as outlined by Kotler et al. (2017: 125). However, since Partipost uses two different platforms, hence the content creation process differs between them. The results and discussions indicate that Kotler’s step by step implementation has been effective in generating impactful content that sustains engagement on Instagram, but it has yet to achieve optimal engagement on the website platform. The lack of engagement on the website is due to several challenges in the content creation stage. Although the company has achieved its goals on Instagram, there are still areas for improvement, particularly in the ideation and content planning stages for better overall performance.Pemasaran tradisional memandang pelanggan sebagai objek pasif dalam interaksi, tetapi teknologi menciptakan pelanggan yang ingin terlibat secara aktif dan memungkinkan brand berinteraksi dengan pelanggan. Salah satu upaya telah efektif digunakan oleh berbagai perusahaan adalah pemasaran digital melalui content marketing. Tidak terkecuali perusahaan startup Partipost. Partipost memberikan layanan berupa platform influencer marketing yang digunakan masyarakat dan brand di berbagai negara salah satunya Indonesia. Perusahaan ini melakukan pemasaran melalui pembuatan konten-konten digital melalui platform seperti, website Partipost yaitu Partipost.com dan Instagram @partipost_id. Pengumpulan data dilaksanakan dengan observasi partisipatif, dokumentasi, dan wawancara tidak berstruktur bersama narasumber-narasumber dari Partipost Indonesia pada periode bulan Juli sampai Desember 2023. Berdasarkan data-data hasil penelitian ditemukan bahwa, alur proses content marketing di Partipost Indonesia secara keseluruhan telah sesuai mengimplementasikan konsep tahapan Content Marketing menurut Kotler dkk. (2017: 125). Namun, content marketing di Partipost memanfaatkan dua platform berbeda sehingga eksekusi pembuatan konten memiliki proses yang berbeda. Hasil dan pembahasan menunjukan implementasi konsep ini mampu menghasilkan konten yang berdampak dalam mempertahankan engagement pada media sosial Instagram, tetapi masih belum menciptakan hasil engagement optimal pada platform website. Hasil engagement pada platform website disebabkan oleh beberapa hambatan pada pelaksanaan content marketing dalam tahapan Penciptaan Konten. Meskipun berhasil mencapai tujuan, content marketing di Instagram masih harus diperbaiki pada tahap Penggagasan dan Perencanaan Konten.